1999
DOI: 10.1046/j.1365-2591.1999.00196.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of various endodontic irrigants on selected microorganisms

Abstract: 5.25% NaOCl was superior in its antimicrobial abilities compared with other irrigants used. A reduced concentration of NaOCl (0.5%) resulted in significantly decreased antimicrobial effects. When compared with 21% alcohol, 0.5% NaOCl and 2% chlorhexidine, paramonochlorophenol (cresophene) showed a greater antimicrobial effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
2
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 26 publications
4
91
2
18
Order By: Relevance
“…Este material foi incubado em anaerobiose, por 48 horas, a 37°C, e a cultura obtida foi semeada em placas contendo BHI ágar [36][37][38] .…”
Section: Estudo In Vitrounclassified
“…Este material foi incubado em anaerobiose, por 48 horas, a 37°C, e a cultura obtida foi semeada em placas contendo BHI ágar [36][37][38] .…”
Section: Estudo In Vitrounclassified
“…119 In contrast, the combination of Calen and CMCP paste was reported 116 as the most effective intracanal medicament compared to a variety of medicaments including 2% CHX solution, Calen paste and 2.5% sodium hypochlorite (NaOCl) for the elimination of E. faecalis and C. albicans using sampling with sterile paper points after 15 days in human teeth. 116 In a study by Ayhan et al, 120 Cresophene (a mix of 30% paramonochloro-phenol, 5% thymol, 0.1% dexamethasone) (Septodont, Saint-Maur, France) had one of the highest levels of antimicrobial activity using agar diffusion when compared with five other irrigants. However, the authors cautioned against using Cresophene due to its known cytotoxic and possible carcinogenic, mutagenic and teratogenic properties.…”
Section: (D) Phenolic Agentsmentioning
confidence: 99%
“…The antibacterial effect of CHX against all the microorganisms in the present study has already been shown (D'Arcangelo et al, 1991). Studies have shown that CHX is effective against bacterial species found in infected root canals, including S. aureus, E. faecalis, S. salivarius, E. coli and C. albicans (Ayhan et al, 1999). …”
Section: Discussionmentioning
confidence: 99%